Carbofuran Cancellation Process - Frederick Fishel (EDIS, 2009)
PI-170, a 4-page illustrated fact sheet by Frederick Fishel, provides a brief history of carbofuran’s use in the United States, describes risks associated with carbofuran use, and outlines the U.S. Environmental Protection Agency’s (EPA) stated rational for revoking its regulations that have allowed carbofuran residues in food. This publication also describes the EPA’s plans announced in 2008 to cancel the pesticide’s registration due to risks carbofuran poses to pesticide applicators and to birds in treated fields. Includes additional sources of information. Published by the UF Department of Agronomy, August 2008.